PENGUKURAN KINERJA PERUSAHAAN PERTANIAN DI LEMBANG, JAWA BARAT DENGAN PENDEKATAN BALANCED SCORE CARD - Fadloli Akhmad; Sudarma Widjaya; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
The purpose of this research was to know financial performance, costumer’s performance, internal business process performance, and employee satisfaction. This research was conducted at a n agricultural company in Lembang, West Java.  This research was a case study in which data was analyzed method by Balanced Score card approach. The data was collected on August 2015. All data was analyzed by quantitative descriptive analysis.  The result showed that the financial performance of the Agricultural Company was on bad category in which scores obtained was only one out of six as a maximum score. The Costumers performance was on good category by obtaining score of five out of six. The Internal Business Process performance category was on quite well in which scores obtained was four. The Employee satisfaction performance category was on quite well, in which scores obtained was two.  In overall showed that the plantation performance was quite well. Key words: balanced scorecard, company performance, hydroponics company